Relevant factors in food shopping behavior: a survey of university students (Research, Society and Development, 2019)
The study of buying behavior, or consumer behavior, is not something new in the social sciences. There is an understanding that from the perspective of the buyer, there are many factors that can influence the choice of a good or service for purchase. It is from this context that the study presents as a general objective: to identify which factors are determinants for the purchase of food for consumption in the food court of a university by the students. The qualitative-quantitative method was used for exploratory and descriptive purposes. And, as a result, it was evidenced that three categories stand out as determining factors for student consumption, they are: (1) perception of consumption based on a cultural motivation among students in the university; (2) perception of influence for consumption coming from social groups formed by colleagues and friends, and finally; (3) perception of consumption as an experience learned based on good or bad experiences in care. Finally, it is concluded that university students find in the consumer culture, in social groups and in their learned experiences, the main factors that influence their behavior of food consumption in the university environment.